KINETIC STUDY ON ADSORPTION OF CHROMIUM(lIl) TO DIATOMACEOUS EARTH PRE-TREATED WITH SULFURIC AND HYDROCHLORIC ACIDS - Nuryono Nuryono; V.V.H. Susanti; Narsito Narsito (Indonesian Journal of Chemistry, 2003)
In this research, the effect of Sangiran diatomaceous earth pre-treatment with sulfuric acid (H2SO4) and hydrochloric acid (HCl) on the kinetics of adsorption for Cr(III) in aqueous solution has been studied. The research has been carried out by mixing an amount of diatomeaeous earth with HCl or H2SO4 in various concentrations for two hours at temperature of 150 - 200°C. The mixture was washed with water until neutral, and the residue was dried at 70°C for four hours. The result then was used as adsorbent. Adsorption was carried out by mixing an amount of adsorbent with Cr(III) solution in various contact times. Ion adsorbed was determined by analyzing filtrate using atomic absorption spectrophotometry. The effect of pre-treatment on adsorption kinetics was evaluated based on kinetic parameters, i.e. constant of adsorption rate by using Langmuir-Hinshelwood kinetics and using two-process kinetics (fast and slow processes). Adsorption kinetics calculated using LH equation gave negative value for adsorption rate constant of zero order (k0). On the other words, the LH kinetics might not be applied for adsorption of Cr(III) to diatomaceous earth adsorbent. Results of kinetics study approached using two processes (fast and slow) showed that adsorption of Cr(III) occurred in two processes with rate constant of fast adsorption, kc, 0.041/min, rate constant of slow adsorption, kl, 0.0089/min, and of slow desorption, k'l, 0.089/menit. Pre-treatment with HCl up to 10 M decreased either kc, kl or k'l, while pre-treatment with H2SO4 1M increased kc to 0.061/min, decreased kl to 0.00424 and k'l to 0.0139/min. On pre-treatment with H2SO4 higher than 6 M significantly decreased three constants above. Based on the Gibbs energy change (4.31 - 6.79 kJ/mole) showed that adsorption involved physical interaction.